The Role of Diagnosis and Treatment of Underlying Liver Disease for the Prognosis of Primary Liver Cancer. (6th September 2017) - Shiani, Ashok; Narayanan, Shreya; Pena, Luis; Friedman, Mark
Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related deaths worldwide. Underlying chronic liver disease has been associated with an increased risk of developing HCC. This study is a review of the current literature regarding the diagnosis, prognostic significance, and role of treating underlying liver disease in patients who are at risk of primary liver cancer. Relevant peer review of the English literature between 1980 and 2017 within PubMed and the Cochrane library was conducted for scientific content on current advances in managing chronic liver diseases and the development of hepatocellular carcinoma. Hepatitis C virus, hepatitis B virus (HBV), nonalcoholic steatohepatitis, autoimmune hepatitis, hereditary hemochromatosis, Wilson disease, primary biliary cirrhosis, α 1-antitrypsin deficiency, and certain drugs lead to an increased risk of developing HCC. Patients with underlying liver disease have an increased incidence of HCC. Hepatitis C virus, HBV, and hemochromatosis can directly lead to HCC without the presence of cirrhosis, while HCC related to other underlying liver diseases occurs in patients with cirrhosis. Treating the underlying liver disease and reducing the progression to cirrhosis should lead to a decreased incidence of HCC.